Profile of nursing diagnoses in people with hypertension and diabetes - Fabiana de Castro Sampaio; Patrícia Peres de Oliveira; Luciana Regina Ferreira da Mata; Juliano Teixeira Moraes; Deborah Franscielle da Fonseca; Vanete Aparecida de Sousa Vieira (Universidad de Antioquia, 2017)
Objective. To identify the profile of nursing diagnoses in people with hypertension and diabetes in primary health care.  Methods. A cross-sectional study involving 175 individuals followed up in eight primary health units of Minas Gerais, Brazil. Data collection was made through interview and physical examination, and diagnostic inference was made according with NANDA-I Taxonomy II. Results. The average age of the users was 62.1 years and the female gender predominated (66.9%). A total of 26 diagnoses were identified, an average of 16 per client (standard deviation=3.9). The most frequent problem-focused diagnosis were: Ineffective Health Management (98.9%), Ineffective Peripheral Tissue Perfusion (78.3%), Sedentary lifestyle (74.3%), Obesity (54.3%) and Insomnia (51.4%). With respect to the defining characteristics and related factors, the average per person was 24 and 28, respectively. Conclusion. In this group of clients, the most frequent diagnoses were in the domain activity/rest. These diagnoses are the basis for planning nursing interventions and provide improved quality of life for these clients.   How to cite this article: Sampaio FC, Oliveira PP, Mata LRF, Moraes JT, Fonseca DF, Vieira VAS. Profile of nursing diagnoses in people with hypertension and diabetes. Invest. Educ. Enferm. 2017; 35(2):139-153.